Stylistic Study of Surah Al-Hujurat : Acquiring the Meaning of Truth - Nunung Nursyamsiah; Hikmah Maulani; Tatang Tatang; Faiz Dzul Fahmi Hamdan (Universitas Pendidikan Indonesia (UPI), 2022)
Today the dissemination of information is very easy to obtain, this much information is often related to problems of daily life so it is often used as a reference to address or solve a problem, maybe even in deciding something. In the context of today's life, there are many cases related to this information issue. This research is to examine more deeply through research on how the meaning of the verses of the Qur'an are related to this information problem in the context we are facing today. This study uses qualitative research related to the process of obtaining correct and accountable information both in relation to humans and to God. This research produces alternative strategies in understanding and responding to analyzing information that is still doxa in nature so as to produce beliefs to be the basis for responding to or following up on the contents of the information